SURVEI SARANA DAN PRASARANA PENDIDIKAN JASMANI DI SMP SE-KECAMATAN CITEURUEP KABUPATEN BOGOR - Tri Gilang Priyo Utomo (Program Studi Pendidikan Jasmani Universitas Negeri Jakarta, 2022)
This study aims to identify and evaluate the condition of physical education facilities and infrastructure in junior high schools in Citeureup District. The research methodology used is a quantitative approach using a survey instrument in the form of a questionnaire. The study was conducted by collecting data directly from physical education teachers in junior high schools in Citeureup District. Data collected includes information on the physical condition of facilities and infrastructure such as sports fields, classrooms, supporting facilities (eg sports equipment, storage warehouses). Analysis of the data obtained and analysis of the data, it can be concluded that the condition of physical education and sports facilities and infrastructure in five junior high schools in Citeureup District, Bogor Regency, is categorized as good with a percentage of 72% and 3 schools with a percentage of 28% are in the less category, although there is still room for improvement in some schools.